Small-signal modeling for phase-shift controlled resonant converters - Li, Xin (2022)
The extended describing function (EDF) method is widely used in modeling the resonant converters. This article finds that the model of the phase-shift controlled resonant converter deduced by this method might be inaccurate especially when the duty-cycle is close to 1. The reason behind it is investigated, showing that derivation of the inverter bridge model based on its fundamental harmonic will cause error. A novel model of the inverter bridge by Fourier analysis is proposed. Incorporating the novel model into the EDF-based resonant model, the accuracy of the phase-shift controlled resonant converter is greatly improved. A series-series compensated inductive power transfer system is fabricated in the lab to verify the validity of the proposed model.